A field guide to the beetles - White, R. E. Richard E. White (New York: Houghton Mifflin, 1983)
A field guide to the beetles, includes over 600 drawings and 65 color paintings portray representative species of the 111 families of North American beetles. Includes information on collecting and preserving beetles.
includes bibliographical references, glossary and index
Keywords: Beetles-north America-identification; Insects-identification; insects north America-identification; Insects-north America-identification